Factors influencing age at menarche – a school based cross sectional study - Narayan Namboothri G; Varghese Iybu Chacko; Rashmi, Anusha; Shreyaswi Sathyanath; Manjula Anil (Indian Journal of Community Health, 2020)
Hormones, life style, animal proteins etc are factors that influence menarche. Like-wise a declining trend in age at menarche has been noticed over the past few years. This study was taken up with the objectives to study factors that are associated with menarche in our study population. Hence a school-based cross-sectional study was undertaken for the same which showed the mean age of menstruation was 12.5 years. It was significantly influenced by milk intake (p <.05). Mothers’ age at menarche was also found to be significantly associated with their daughters’ age at menarche. Conclusion: This study provides an insight into determining factors affecting age of menarche, focusing on dietary and maternal factors. Milk consumption was found to be an important factor.